2011
DOI: 10.1111/j.1463-1318.2010.02405.x
|View full text |Cite
|
Sign up to set email alerts
|

Medium-term results of stapled transanal rectal resection (STARR) for obstructed defecation and symptomatic rectal-anal intussusception

Abstract: STARR was successful for the treatment of selected patients with ODS and IRP. Postoperative faecal urgency rapidly decreases with time. It is not possible to predict who will develop urgency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 24 publications
(52 reference statements)
4
22
1
Order By: Relevance
“…Fecal urgency remains a problem in low rectal stapling procedures [18], [19]. The results of this prospective study coincide with the data of the Italian group of Naldini et al [8].…”
Section: Discussionsupporting
confidence: 83%
“…Fecal urgency remains a problem in low rectal stapling procedures [18], [19]. The results of this prospective study coincide with the data of the Italian group of Naldini et al [8].…”
Section: Discussionsupporting
confidence: 83%
“…A detailed analysis of the individual components of the ODS score in this subgroup of patients has also revealed that two of the most common symptoms of a symptomatic rectocoele, the need to strain at stool and manual digitation, were significantly reduced, together with a trend toward improvement in perineal discomfort. Interestingly, in a recent report by Goede et al [27] on the efficacy of stapled transanal rectal resection for ODS from a prospective database of more than 300 patients, the authors also defined an ODS score of < 6 as being 'low', albeit with no explanation or reason provided. In the light of our findings, this cut-off value of 6 is a possible validation for use in future studies.…”
Section: Discussionmentioning
confidence: 96%
“…In a prospective randomized trial LEHUR et al (22) showed a superior effectiveness of STARR compared to biofeedback for patients with internal rectal prolapse and ODS. Different registries compiling data from several single centre experiences further demonstrated the efficacy of STARR (19,30,31) The findings in this systematic review and meta-analysis underscore the efficacy of this surgical procedure to treat ODS but at the same time reveal different shortcomings in published data.…”
Section: Discussionmentioning
confidence: 85%
“…Fifteen studies have used the Cleveland Constipation Score (CCS) (17, 18, 21, 28, 39-41, 43, 45, 46, 48-50, 53, 54). Altomare-score, Longo-score, and the obstructed defecation syndrome-score (ODS-score), or a self-reported or modified ODS-score (S-ODS or M-ODS) were also used in three (23,38,46) seven (39,40,43,46,47,52,53) and eight studies (24,26,30,37,42,49,50,51) respectively (Table 3). An overview of the instruments (scoring system) is presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation